Effectiveness of the putri self-management module in improving knowledge, attitudes, and blood glucose levels among patients with type 2 diabetes mellitus - Ratna Indah Sari Dewi; Ramah Hayu; Herman Susilo; Putri Dafriani (Science Midwifery, 2026)
Poor glycemic control among patients with Type 2 Diabetes Mellitus (T2DM) is often associated with inadequate diabetes knowledge, low self-efficacy, and suboptimal self-management practices. The PUTRI (Pemberdayaan Untuk Tatalaksana dan Regulasi Individu) module was developed as a structured educational tool to support diabetes self-management in primary care settings. This study aimed to evaluate the effectiveness of the PUTRI module on patients’ knowledge, attitudes, and random blood glucose (RBG) levels. A quasi-experimental one-group pretest–posttest study was conducted among 50 patients with T2DM enrolled in a chronic disease management program at a primary healthcare center. Participants received a 7-day intervention using the PUTRI module. Knowledge and attitude were assessed using structured questionnaires, while RBG levels were measured using calibrated glucometers. Data were analyzed using the Wilcoxon Signed-Rank Test and Spearman’s correlation analysis. Significant improvements were observed in knowledge scores (0.176 ± 0.222 vs. 0.940 ± 0.121; p<0.001) and attitude scores (1.95 ± 0.505 vs. 2.91 ± 0.252; p<0.001) following the intervention. Mean RBG levels decreased from 267.54 mg/dL at baseline to 185.52 mg/dL on Day 7 (p<0.001). A moderate positive correlation was identified between post-test knowledge and attitude scores (rs=0.566, p<0.001), while self-efficacy was negatively correlated with Day-7 RBG levels (rs=-0.282, p=0.047). The PUTRI module was associated with improvements in diabetes-related knowledge, attitudes, and short-term glycemic outcomes among patients with T2DM. Further studies using randomized controlled designs and longer follow-up periods are recommended to confirm these findings.